IT Sector: Opportunities for the German-Nigerian Economic and Development Partnership - Johannes Paha; Lydia Wolter (Wirtschaftsdienst)
Abstract The emergence and growth of the largest African market for information and communication technology in Lagos, Nigeria, is based on agglomeration effects and the interaction between complementary success factors that have positive externalities. Necessary reforms that are supposed to be implemented through national measures to eliminate market failures as well as international measures in development policy require a market transition into the formal economy. However, this necessity runs the risk of destroying the successful interplay between the factors of success. This article illustrates the opportunities and risks for German-Nigerian economic and development cooperation.